2020
DOI: 10.1029/2019wr026820
|View full text |Cite
|
Sign up to set email alerts
|

Pedotransfer Function for the Brunswick Soil Hydraulic Property Model and Comparison to the van Genuchten‐Mualem Model

Abstract: Modeling soil hydraulic properties requires an effective representation of capillary and noncapillary storage and conductivity. This is made possible by using physically comprehensive yet flexible soil hydraulic property models. Such a model (Brunswick [BW] model) was introduced by Weber et al. (2019, https://doi.org/10.1029/2018WR024584), and it overcomes some core deficiencies present in the widely used van Genuchten-Mualem (VGM) model. We first compared the performance of the BW model to that of the VGM mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 98 publications
0
39
0
Order By: Relevance
“…Based on these results, it can be concluded that the soils identified as bimodal could have been more accurately described by considering dual‐porosity models in the PTF development of Rosetta (Schaap et al., 2001), Rosetta3 (Zhang & Schaap, 2017), in the PTF of Vereecken (Vereecken et al, 1989, 1990) and Weynants (Weynants et al., 2009), as well as those of euptfs (Tóth et al., 2015; Szabó et al., 2021) and Weber et al. (2020), as they used, or partly used, either the UNSODA, Vereecken, or EU‐HYDI dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, it can be concluded that the soils identified as bimodal could have been more accurately described by considering dual‐porosity models in the PTF development of Rosetta (Schaap et al., 2001), Rosetta3 (Zhang & Schaap, 2017), in the PTF of Vereecken (Vereecken et al, 1989, 1990) and Weynants (Weynants et al., 2009), as well as those of euptfs (Tóth et al., 2015; Szabó et al., 2021) and Weber et al. (2020), as they used, or partly used, either the UNSODA, Vereecken, or EU‐HYDI dataset.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the findings of this study suggest that the impact of the model structure (e.g., Weber et al, 2020;Rudiyanto et al, 2021) and limited observations has to be considered in PTF development. However, to further improve the PTFs that predict SHPs over the entire moisture range, a much broader dataset and the impact of the soil structure such as the presence of macropore need to be considered.…”
Section: Limitations Of the Model Structure And Shp Observations In P...mentioning
confidence: 80%
“…Weber et al. (2020) recently developed a transfer function through weighted linear regression to predict the parameters of the so‐called Brunswick model provided by Weber et al. (2019) from the VGM parameters.…”
Section: Introductionmentioning
confidence: 99%
“…GIF Mod applies the Van Genuchten-Mualem equation to estimate catchment wide storage, which identifies catchment storage based on the relationship between storage and water head (Onoja et al, 2019;Weber et al, 2020). In HEC-HMS storage is computed by various equations revealing the relationship between storage and other variables such as catchment area, elevation and discharge (https://www.hec.…”
Section: Storagementioning
confidence: 99%